2000
DOI: 10.1097/00002030-200004140-00007
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance, viral burden, insulin-like growth factor-1, interleukin-6 and growth impairment in children infected with human immunodeficiency virus

Abstract: Differences in energy expenditures were not found between normal and growth-impaired HIV-infected children. Energy intake but not energy expenditure was significantly reduced when HIV-infected children were compared to expected normal values for age and gender. Advanced HIV clinical disease, severe immune suppression, increased viral burden, increased IL-6 activity, decreased total serum protein, and decreased IGF-1 levels were more likely to be found in HIV-infected children with growth impairment in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Markedly decreased levels of circulating IGFBP-3 have been found in patients with systemic JIA [15, 16, 17], Crohn’s disease or cystic fibrosis [18, 19]. Some observations in human diseases suggest a direct relationship between increased IL-6 and reduced IGFBP-3 with chronic overproduction of IL-6 being responsible for the decrease in circulating IGFBP-3: (a) the inverse correlation of intact IGFBP-3 with serum IL-6 levels and with clinical and laboratory parameters of disease activity; (b) the close relation of a rapid fall in IL-6 and C-reactive protein levels with a significant increase in IGFBP-3 levels following elementary diet in Crohn’s disease [18, 20], and (c) the correlation between IL-6 production and decreased levels of IGF-I and IGFBP-3 in HIV-infected children with decreased height velocity [21, 22]. …”
Section: Abnormalities Of the Insulin-like Growth Factor-i System In mentioning
confidence: 99%
“…Markedly decreased levels of circulating IGFBP-3 have been found in patients with systemic JIA [15, 16, 17], Crohn’s disease or cystic fibrosis [18, 19]. Some observations in human diseases suggest a direct relationship between increased IL-6 and reduced IGFBP-3 with chronic overproduction of IL-6 being responsible for the decrease in circulating IGFBP-3: (a) the inverse correlation of intact IGFBP-3 with serum IL-6 levels and with clinical and laboratory parameters of disease activity; (b) the close relation of a rapid fall in IL-6 and C-reactive protein levels with a significant increase in IGFBP-3 levels following elementary diet in Crohn’s disease [18, 20], and (c) the correlation between IL-6 production and decreased levels of IGF-I and IGFBP-3 in HIV-infected children with decreased height velocity [21, 22]. …”
Section: Abnormalities Of the Insulin-like Growth Factor-i System In mentioning
confidence: 99%
“…There are overlapping effects on growth resulting from a vicious cycle between malnutrition and HIV infection. Malnutrition impairs the immune system and weakens the body’s defences, leading to HIV disease progression ; while HIV infection, related opportunistic infections and chronic inflammation may weaken nutritional status . Repeated episodes of malnutrition during infancy and childhood may have occurred frequently among APH, and lifelong HIV infection can lead to chronic malnutrition and growth retardation as APH age into adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…In previous experiments, there have been variable inflammatory immune responses to malnutrition. Decreased plasma TNFa production has been reported in rodent models of protein-energy malnutrition (Chan et al 1996, Schaffer et al 1997, Anstead et al 2001, but increased plasma IL6 concentration has been observed in malnourished patients (Malave et al 1998, Johann-Liang et al 2000, de Martino et al 2000. In addition, maternal dietary protein restriction decreased NO synthase (NOS) in endometrium and placenta of pigs during early gestation (Wu et al 1998).…”
Section: Discussionmentioning
confidence: 99%